2006
DOI: 10.3732/ajb.93.1.110
|View full text |Cite
|
Sign up to set email alerts
|

Spectral reflectance of Thalassia testudinum (Hydrocharitaceae) seagrass: low salinity effects

Abstract: Massive anthropogenic changes in estuarine salinities, from manipulations of freshwater flows, are again occurring through governmental projects “correcting” past freshwater alterations. The downstream effects of increased freshwater on seagrass meadows, a major fisheries and ecosystem habitat, are not clear. Spectral responses to low salinities were quantitatively delimited for the important habitat seagrass Thalassia testudinum utilizing spectral reflectance measurements for the first time (non‐invasive samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
2
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 49 publications
1
22
2
3
Order By: Relevance
“…Pantulan pada saluran NIR juga tidak setinggi pada daun Ea tanpa epifit. Temuan serupa juga diperoleh oleh Thorhaug et al (2002;2003;2006) Pada daun Ea yang rusak, respon spektral hampir mirip dengan daun Ea ber-epifit, dimana puncak pantulan bergeser pada panjang gelombang yang lebih panjang yaitu 590 nm dan puncak yang lebih rendah pada 656 nm. Namun, perbedaannya adalah kenaikan respon spektral terjadi pada semua saluran tampak.…”
Section: Enhalus Acoroidesunclassified
See 2 more Smart Citations
“…Pantulan pada saluran NIR juga tidak setinggi pada daun Ea tanpa epifit. Temuan serupa juga diperoleh oleh Thorhaug et al (2002;2003;2006) Pada daun Ea yang rusak, respon spektral hampir mirip dengan daun Ea ber-epifit, dimana puncak pantulan bergeser pada panjang gelombang yang lebih panjang yaitu 590 nm dan puncak yang lebih rendah pada 656 nm. Namun, perbedaannya adalah kenaikan respon spektral terjadi pada semua saluran tampak.…”
Section: Enhalus Acoroidesunclassified
“…Hasil penelitian ini dapat dibandingkan dengan penelitian yang telah dilakukan sebelumnya, antara lain oleh Fyfe (2003), Thorhaug et al (2002;2003;2006;2007 Thorhaug et al (2002;2003) menemukan bahwa ada pergeseran lokasi red-edge pada Thalassia sp. dan spesies lamun lain saat mengalami stres dan penuaan, dimana keduanya berhubungan dengan berkurangnya kandungan klorofil dalam daun.…”
Section: Perbandingan Respon Spektral Ea Dan Crunclassified
See 1 more Smart Citation
“…Despite their environmental and economic significance, seagrass populations are threatened worldwide by coastal development and eutrophication and may be nearing a crisis with respect to global sustainability [7]. The land-water interaction along coasts is influenced by freshwater networks where hydrologic impacts to seagrass ecosystems include increases in nutrients such as nitrogen and phosphorus occurring from industrial or agricultural sources [8], sediment discharge from watershed deforestation and mangrove clearing [8], and disruption of the natural salinity regime [2,9]. Without appropriate management, widespread loss of seagrass habitats is predicted to continue [10], especially given continued development of coastal lands.…”
Section: Introductionmentioning
confidence: 99%
“…Under water stress, and the change of plant spectral reflectance in the near-infrared range has been reported in some other researches (Holben et al, 1983;Jackson et al 1985;Moran et al, 1989;Yamamoto et al, 1995;Penuelas et al , 1999). Thorhaug et al (2006) stated that browning and necrosis resulted in a clear change in the shape of the reflectance spectra of Thalassia blades and suggested that the reflectance spectra at 750 nm might be a suitable stress index. Riedell et al (1995) noted that crop canopy chlorosis and necrosis in small grain fields infested with greenbugs, etc.…”
mentioning
confidence: 99%